2012
DOI: 10.1590/s0100-879x2012007500054
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture and characterization of alveolar bone osteoblasts isolated from type 2 diabetics

Abstract: In order to understand the mechanisms of poor osseointegration following dental implants in type 2 diabetics, it is important to study the biological properties of alveolar bone osteoblasts isolated from these patients. We collected alveolar bone chips under aseptic conditions and cultured them in vitro using the tissue explants adherent method. The biological properties of these cells were characterized using the following methods: alkaline phosphatase (ALP) chemical staining for cell viability, Alizarin red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Further, the analysis of alveolar bone osteoblasts isolated from T2DM patients correlated with the negative modulation of the gene expression of COL-I. 26 One possible pathway involves the interaction between AGE and its receptor (RAGE), which may interfere with COL-I expression, impairing the adhesion of osteoblasts to the extracellular bone matrix and, therefore, compromising their normal bone-forming activity. 14 The results of our study also showed reduced expression of BSP, which is important in bone matrix mineralization, in the bone biopsies of individuals with T2DM compared to systemically healthy individuals (P < 0.05, Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…Further, the analysis of alveolar bone osteoblasts isolated from T2DM patients correlated with the negative modulation of the gene expression of COL-I. 26 One possible pathway involves the interaction between AGE and its receptor (RAGE), which may interfere with COL-I expression, impairing the adhesion of osteoblasts to the extracellular bone matrix and, therefore, compromising their normal bone-forming activity. 14 The results of our study also showed reduced expression of BSP, which is important in bone matrix mineralization, in the bone biopsies of individuals with T2DM compared to systemically healthy individuals (P < 0.05, Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…Periodontal ligament cells are composed of heterogeneous cell populations, including fibroblasts, osteogenic or PDL progenitor cells, and the latter in particular can differentiate into osteoblasts [20,21]. The sources of osteoblasts are very limited in alveolar defect areas [22,23], and some studies suggested that the pre-existing osteoblastic cells in alveolar defect areas only make a small contribution to the regeneration of the new bone, while the recruitment and proliferation of osteogenic or PDL progenitor cells and subsequently their differentiation into osteoblasts are the principal mechanism for the formation of new bone [24,25]. The increased viability of hPDL cells treated with HFC in our study suggests potential in HFC regarding the repair of alveolar bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…The Runx-2 and Col-1 mRNA levels in the T2DM group were lower than in normal humans, suggesting that diabetes reduced osteogenic differentiation. BGP and Col-1 are protein frameworks that compose bone tissue, and could be specific markers for bone tissue formation (Sanguineti et al, 2008;Sun et al, 2012). The secretion of BGP and Col-1 in osteoblasts from T2DM patients was lower than in healthy human.…”
Section: Discussionmentioning
confidence: 99%